Hydrodynamics strongly affect the dynamics of colloidal gelation but not gel structure. Issue 1 (30th November 2018) - de Graaf, Joost; Poon, Wilson C. K.; Haughey, Magnus J.; Hermes, Michiel
Abstract : The gel network formed by attractive colloids is largely set by the pre-existence of structures upon quenching the system. Abstract : Colloidal particles with strong, short-ranged attractions can form a gel. We simulate this process without and with hydrodynamic interactions (HI), using the lattice-Boltzmann method to account for presence of a thermalized solvent. We show that HI speed up and slow down gelation at low and high volume fractions, respectively. The transition between these two regimes is linked to the existence of a percolating cluster shortly after quenching the system. However, when we compare gels at matched 'structural age', we find nearly indistinguishable structures with and without HI. Our result explains longstanding, unresolved conflicts in the literature.